The New ISP Webster Philippine's comprehensive dictionary. ([S.l.] Kimball Enterprises, 2001)
Published by the International Standard Publishing, it is the 1st and only Philippine comprehensive dictionary as of publication. It contains 8 major languages that include Tagalog, Bikolano, Cebuano, Hiligaynon, Illongo, Pampango, and Pangasinan dialects.
Jointly published with Environmental Cleanliness and Regreening (ENCLEARE) Foundation, Inc.
Keywords: English language -- Philippine languages. -- Dictionaries; English language -- Synonyms and antonyms; Computers -- Terminology